ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR READ ALOUD BAGI LITERASI EMERGEN - Sujono, Hartin Rizky; S. Damaianti, Vismaia; Abidin, Yunus (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Literacy becomes a global concern including in Indonesia. Literacy in Indonesia still needs improvement. The attempt that should not be left in enhancing children’s literacy in Indonesia is the stimulation on young children. In this process, family becomes the main gate which could be acted as the foundation of literacy which is called emergent literacy. Enhancing emergent literacy can optimize their forthcoming literacy development. One of the activities that is believed could support the maturity of emergent literacy phase is read aloud. However, there is no learning materials related about read aloud which can bridging family literacy practitioner and young children to stimulate reading literacy in specific. Therefore, this research attempt to analyze the need of learning materials based on two perspectives which are family literacy practitioner and young children with the age of 3 to 6 years old. Utilizing qualitative research method, with collecting data using questionnaire which were filled by 20 literacy family practitioner. Interviewing 12 boys and girls in total. The result of this research shows from family literacy point of view which is expecting learning material contains clear instruction, interactive contents, reading stimulation, and in the form of children picture book. From the children perspectives shows that there was a need to start forming the story from the theme, the characters, the compulsory component, the material of picture story book, and the appearance of emergent literacy development for young children in the age of 3 to 6 years old particularly in reading literacy.